1975
DOI: 10.1126/science.1114318
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic Matching by Pigeons: Rate of Learning Complex Discriminations Predicted from Simple Discriminations

Abstract: Pigeons had no greater difficulty learning a complex discrimination involving arbitrary among stimuli (symbolic matching) than one involving interrelations based on stimulus similarity (matching-to-sample). The relative rates of acquisitions of matching and symblic matching may be accounted for by the discriminability between sample stimuli and between comparison stimuli, with the former playing the more important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
142
1
5

Year Published

1982
1982
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(164 citation statements)
references
References 6 publications
14
142
1
5
Order By: Relevance
“…The overall lower level of accuracy found with trials involving line tilts or shapes than found with trials using only colors may result from greater difficulty in discriminating line tilts or shapes than in discriminating colors. Carter and Eckerman's (1975) analysis of symbolic matching suggested further that matching would be more difficult when line tilts or shapes appeared as sample stimuli and had to be discriminated successively than when they appeared as comparison stimuli and had to be discriminated simultaneously. Their analysis suggests that performance should be higher in our OTM condition, in which line tilts and shapes are used as comparison stimuli, than in our MTO condition, in which line tilts and shapes are used as sample stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The overall lower level of accuracy found with trials involving line tilts or shapes than found with trials using only colors may result from greater difficulty in discriminating line tilts or shapes than in discriminating colors. Carter and Eckerman's (1975) analysis of symbolic matching suggested further that matching would be more difficult when line tilts or shapes appeared as sample stimuli and had to be discriminated successively than when they appeared as comparison stimuli and had to be discriminated simultaneously. Their analysis suggests that performance should be higher in our OTM condition, in which line tilts and shapes are used as comparison stimuli, than in our MTO condition, in which line tilts and shapes are used as sample stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…As Carter and Eckerman (1975) pointed out, the matching-to-sample task includes two basic discriminations.…”
Section: Methodsmentioning
confidence: 99%
“…In arbitrary (generalized) matching, the sample and the comparison do not share identical features, for example, selecting a circle in the presence of a blue sample. In both examples selecting a comparison is strengthened in the presence of the sample, with the identity relations between colors in the first being ignored in the second (Carter & Eckerman, 1975;Cohen et. al., 1981;Lowenkron, 1991).…”
Section: Manded Stimulus Selection Like Much Verbalmentioning
confidence: 99%